When Gold Blossoms : Indian jewelry from the Susan L. Beningson Collection - Asia Society (2004)
[Dt.:]In dieser Online-Ausstellung werden Exponate aus der Susan L. Beningson Collection gezeigt. Dabei handelt es sich um Schmuckstücke aus Südindien. Ausgewählt wurden insgesamt 19 Stücke, die hier bildlich ausgestellt werden. Verantwortlich für die Ausstellung ist die Asia Society mit Sitz in New York. Zudem ist es möglich, eine Nachbesprechung der Ausstellung von der Kunsthistorikerin Julie Rauer zu lesen. - [Engl.:] The ehibition "When Gold Blossoms" presents of the Susan L. Beningson collection of Indian jewelry. The focus of the collection is gold jewelry from the south of India, in particular, jewelry for deities and women. The collection began with a necklace that Beningson bought to wear and a pair of earrings that she found to match. It is a collection based not on academic principle but on the pleasures of seeing, touching, and wearing. When Gold Blossoms gives us the chance to share in the wearers' pleasures with careful, close viewing.